Large ungulate effects on nitrogen dynamics in riparian ecosystems of Colorado - Przeszlowska, Agnieszka, author; Trlica, M. J., advisor (Colorado State University. Libraries, 2008)
Large ungulates can affect feedbacks between aboveground and belowground N pools, nutrient mineralization rates, and soil food webs at different temporal and spatial scales. Little is known about the effects of ungulates on nutrient dynamics in riparian zones which are important systems that provide habitat and forage for wildlife and livestock, and act as sediment and nutrient buffers between terrestrial and aquatic ecosystems. Livestock grazing is a predominant land use on public and private lands in the western US while bison are more prevalent in National Parks and Monuments. The main goal of my studies was to investigate if bison and cattle alter N dynamics in riparian ecosystems of the Great Sand Dunes region or Sheep Creek of north-central Colorado. Studies of terrestrial ecosystems have shown accelerating, decelerating, or neutral effects of ungulates on N cycling (N pools or N fluxes). I hypothesized that cattle or bison grazing would accelerate N cycling in riparian zones because they are fertile and productive systems. Bison grazing in Great Sand Dunes riparian corridors and wet meadows did not increase potential net N mineralization while cattle did not affect net N mineralization in wet meadows. Cattle grazing in the Sheep Creek montane riparian zone did not increase aboveground production, aboveground or belowground plant N pools, soil N pools, soil microbial biomass, litter decomposition, net N mineralization or denitrification in the riparian zone as a whole. Cattle also did not affect stream or groundwater NO3- and NH4+ concentrations. Signs of accelerated N cycling were detected only near the stream bank where potential soil net N mineralization was 35% higher in cattle grazed than excluded sites. This could be attributed to more frequent cattle utilization of streambank sites compared with areas further away from the stream. Although there was no strong evidence for accelerated N cycling in riparian zones grazed by bison or cattle, results suggest that increased N cycling is more likely in riparian sites that have a long history of grazing or are grazed frequently at moderate intensity. Season-long, light-to-moderate cattle grazing does not appear detrimental to N cycling and riparian functioning.
Keywords: bison; cattle grazing; herbivory; nitrogen cycling; riparian; ungulates; ecology; soil sciences; range management